2019
DOI: 10.1242/jeb.200410
|View full text |Cite
|
Sign up to set email alerts
|

Turtles maintain mitochondrial integrity but reduce mitochondrial respiratory capacity in the heart after cold-acclimation and anoxia

Abstract: Mitochondria are important to cellular homeostasis, but can become a dangerous liability when cells recover from hypoxia. Anoxiatolerant freshwater turtles show reduced mitochondrial respiratory capacity and production of reactive oxygen species (ROS) after prolonged anoxia, but the mechanisms are unclear. Here, we investigated whether this mitochondrial suppression originates from downregulation of mitochondrial content or intrinsic activity by comparing heart mitochondria from (1) warm (25°C) normoxic, (2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 65 publications
2
34
1
Order By: Relevance
“…For adult turtles, observed changes in ETS component proteins induced by cold-acclimation may play a role in the metabolic preparations that enhance anoxia survival at low temperature. For example, the adultspecific decrease in several component proteins of complexes II, III, and V with coldacclimation would reduce the overall aerobic capacity of the heart and may contribute, at least in part, to the observed reduction in respiration rates of isolated mitochondria (Bundgaard et al, 2019; Galli et al, 2013) and the lower cellular ATP content (Stecyk et al, 2009) of cold-acclimated adult turtles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For adult turtles, observed changes in ETS component proteins induced by cold-acclimation may play a role in the metabolic preparations that enhance anoxia survival at low temperature. For example, the adultspecific decrease in several component proteins of complexes II, III, and V with coldacclimation would reduce the overall aerobic capacity of the heart and may contribute, at least in part, to the observed reduction in respiration rates of isolated mitochondria (Bundgaard et al, 2019; Galli et al, 2013) and the lower cellular ATP content (Stecyk et al, 2009) of cold-acclimated adult turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial remodeling also plays a key role in managing metabolic depression (Bundgaard et al, 2020; St-Pierre et al, 2000; Stuart et al, 1998). For example, mitochondrial respiration rates are reduced in the brain and heart of cold-acclimated turtles without altering mitochondrial content or structure (Bundgaard et al, 2019; Pamenter et al, 2016). Rather, suppressing mitochondrial activity may be achieved by a non-specific decrease in substrate utilization across the electron transport system (ETS) (Bundgaard et al, 2019), or via targeted reductions in proton leak and ATP synthase activity (Galli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birds have a relatively long lifespan considering their high metabolic activity and small body size, and it is shown that birds have less ROS production and longer telomeres (Hickey et al, 2012). Similarly, it has been noted that hypoxia in the freshwater turtle Trachemys scripta elegans inhibits mitochondrial respiration and ROS production, preventing oxidative damage (Bundgaard et al, 2019). These examples illustrate that different species have different ways to maintain mitochondrial function in the face of physiological challenges, and thereby sustain a relatively long and healthy lifespan.…”
Section: Integrating the Hallmarks Of Aging Across The Tree Of Lifementioning
confidence: 99%
“…IGA is applicable to eukaryotic organisms, e.g. turtle (Bundgaard et al, 2019), bovine, yeast (Ladig et al, 2011), potato (Eubel et al, 2004) and Drosophila (Elkholi et al, 2019). Using western blot analysis, it was reported that supercomplex formation was enhanced in genetically adipogenic differentiated human mesenchymal stem cells (Hofmann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%